Intelligent Emotion Tracking System VIRE: Evaluation of Neural Network Architectures in Facial Emotion Recognition - da Silva, Nathan Ferraz; Filho, Geraldo Pereira Rocha; Immich, Roger; Gonçalves, Vinícius Pereira; Meneguette, Rodolfo Ipolito (Journal of the Brazilian Computer Society, 2026)
This work proposes an emotional monitoring system called Visual Identification of Recognition of Emotions (VIRE), based on convolutional neural networks (CNNs) to analyze facial expressions. Using the six basic emotions proposed by Paul Ekman as a reference, which can be identified from the composition of various facial muscle states, VIRE aims to assist in the diagnosis of mental health conditions. While emotional expressions are communicated in various ways, this research focuses primarily on facial expressions due to their expressiveness resulting from the mobility of facial muscles. The methodology involved collecting data from the FER2013 dataset, preprocessing the images, hyperparameter tuning, and training three different architectures: AlexNet, DenseNet, and a custom CNN. The research will classify expressions into basic emotions and evaluate the models' performance in terms of accuracy and other metrics. VIRE has demonstrated potential, achieving an accuracy of about 60%, although improvements are needed for practical application. The ultimate goal is to create a tool that integrates technology and health, facilitating the identification of emotional states that may indicate mental health issues, thereby contributing to more accurate and effective diagnoses.